Mengontrol Kebebasan Perilaku Menggunakan Teknologi Digital dengan Digital Detox - Astrid Kusuma Rahardaya; Firman Kurniawan (JURNAL LENSA MUTIARA KOMUNIKASI, 2022)
The development of the times led to the emergence of various kinds of digital technology that can be accessed easily. The emergence of various kinds of digital technology has become an important need for many people. Its use cannot be separated from everyday life. The frequency of using digital technology that cannot be controlled, results in various kinds of adverse effects on humans, one of which can lead to digital addiction. Although in essence humans are free creatures and have the freedom to behave in their daily lives, if this freedom is not controlled properly it will be detrimental to many parties. To overcome this, the need for digital fasting or Digital Detox so that humans can control their freedom in the use of digital technology.